2002
DOI: 10.1111/1467-9965.02001
|View full text |Cite
|
Sign up to set email alerts
|

Exponential Hedging and Entropic Penalties

Abstract: e solve the problem of hedging a contingent claim B by maximizing the expected exponential utility of terminal net wealth for a locally bounded semimartingale X . We prove a duality relation between this problem and a dual problem for local martingale measures Q for X where we either minimize relative entropy minus a correction term involving B or maximize the Q-price of B subject to an entropic penalty term. Our result is robust in the sense that it holds for several choices of the space of hedging strategies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
353
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 304 publications
(365 citation statements)
references
References 26 publications
11
353
0
1
Order By: Relevance
“…The problem of expected utility maximization in incomplete markets has been widely studied in the mathematical finance literature in recent years, and it has been shown that there is a duality relationship between maximization of expected utility and minimization of an appropriate divergence (e.g., Frittelli 2000, Rouge and El Karoui 2000, Goll and Rüschendorf 2001, Delbaen et al 2002, Slomczyński and Zastawniak 2004, Ilhan et al 2008, Samperi 2005. Most of this literature has focused on the case of exponential utility, for which the dual problem is the minimization of the reverse KL divergence D KL q p , as well as on issues that arise in multiperiod or continuous-time markets.…”
Section: Utility/entropy Duality In Incomplete Marketsmentioning
confidence: 99%
“…The problem of expected utility maximization in incomplete markets has been widely studied in the mathematical finance literature in recent years, and it has been shown that there is a duality relationship between maximization of expected utility and minimization of an appropriate divergence (e.g., Frittelli 2000, Rouge and El Karoui 2000, Goll and Rüschendorf 2001, Delbaen et al 2002, Slomczyński and Zastawniak 2004, Ilhan et al 2008, Samperi 2005. Most of this literature has focused on the case of exponential utility, for which the dual problem is the minimization of the reverse KL divergence D KL q p , as well as on issues that arise in multiperiod or continuous-time markets.…”
Section: Utility/entropy Duality In Incomplete Marketsmentioning
confidence: 99%
“…It is related to the portfolio choice problem: under indifference valuation, the price of a claim is such that the agent is indifferent between selling and not selling the claim, provided that each of the two alternatives is combined with an optimal portfolio choice that maximizes utility. Particularly popular is exponential indifference valuation due to its analytical tractability on the one hand -the exponential form induces a convenient translation invariance property -and its theoretically appealing properties, especially in a dynamic context, on the other (El Karoui and Rouge [24], Delbaen et al [18], Kabanov and Stricker [42], Mania and Schweizer [53]). See also Hu, Imkeller and Müller [38], Becherer [4], Morlais [57,58], and Cheridito and Hu [12] for recent work on the problems of portfolio choice and indifference valuation.…”
Section: Introductionmentioning
confidence: 99%
“…We follow Tehranchi (2004), and define A as the set of strategies p satisfying E sup t2½0;T expðÀg 0 X p t Þo1 for some g 0 4g. There are other possible characterisations of admissibility in exponential utility maximisation problems, and these are discussed in depth in Delbaen et al (2002) and Schachermayer (2001), to which the interested reader is referred.…”
Section: Article In Pressmentioning
confidence: 99%
“…It is well known (for example Delbaen et al, 2002;Schachermayer, 2001) that the value functions uðxÞ and vðyÞ are conjugate:…”
Section: Article In Pressmentioning
confidence: 99%